(untitled) (Bangladesh Journal of Medicine, 2021)
Brucellosis is a Zoonotic disease which is not so common health problem in Bangladesh. For its variable presentation it creates diagnostic challenge for the clinicians. Although Brucellosis is a treatable and curable condition sometimes delay in diagnosis and lack of insight for the disease creates high morbidity. In this case report we have presented a case of brucellosis presented with prolong fever, joint pain with complications which created dilemma in diagnosis in a tertiary care private hospital of Dhaka. The purpose of presenting this case report is to create concern among the clinicians regarding the variablepresentation of Brucellosis& emphasizing to clinical judgment over investigations, especially in limited resources. Bangladesh J Medicine July 2022; 33(1) : 89-93